A photocatalyst nano antibacterial nonwoven material and preparation method thereof

By using a combination of multi-layer polypropylene antibacterial nanofiber nonwoven material and nanophotocatalyst composite coating in polyolefin filamentous materials, the application problem of antibacterial materials in polyolefin filamentous materials is solved, and efficient antibacterial effect is achieved and good mechanical properties.

CN110228250BActive Publication Date: 2025-01-07JIANGSU SHENGFANG NANO MATERIAL TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN201910582453.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2019-06-29
Publication Date
2025-01-07
Estimated Expiration
2039-06-29

AI Technical Summary

Technical Problem

When existing antibacterial materials add loaded silver antibacterial agents to polyolefin filamentous materials, it is difficult to control the particle size, poor water absorption, resulting in insufficient contact with the tested bacterial species, difficult to meet the antibacterial effect, and poor heat resistance of organic antibacterial agents , low safety.

Method used

At least two layers of polypropylene antibacterial nanofiber nonwoven material are used, each layer is coated with a nanophotocatalyst composite coating, and a breathable layer is provided between the two layers to increase breathability and antibacterial effect. The fiber fineness is 1 to 3 The thickness of the nanophotocatalyst composite coating is 0.01 to 0.03 mm, the thickness of the breathable layer is 0.4 to 0.5 mm, and the micropore pore diameter is 50 to 100 nm.

Benefits of technology

Achieving long-lasting and effective antibacterial properties, strength and softness, C4 dissolution antibacterial rate is greater than or equal to 95%, C5 non-dissolution antibacterial rate difference is greater than or equal to 25%, transverse tensile strength is greater than 27N, and longitudinal tensile strength is greater than or equal to 25%. More than 40N, softness is less than 35mN, transverse and longitudinal extension is greater than 92%, and whiteness is greater than or equal to 92%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN110228250B_ABST
    Figure CN110228250B_ABST
Patent Text Reader

Abstract

The present invention provides a photocatalyst nano antibacterial nonwoven material and a preparation method thereof. The photocatalyst nano antibacterial nonwoven material of the present invention comprises at least two layers of polypropylene antibacterial nanofiber nonwoven material layers, the surface of each layer of the polypropylene antibacterial nanofiber nonwoven material layer is coated with a nano photocatalyst composite coating, and an air permeable layer is arranged between two adjacent layers of the polypropylene antibacterial nanofiber nonwoven material layers, and the air permeable layer is provided with a plurality of micropores. The photocatalyst nano antibacterial nonwoven material prepared by the present invention has long-lasting and effective antibacterial performance, strength and softness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nonwoven materials, and in particular to a photocatalyst nano antibacterial nonwoven material and a preparation method thereof. Background Art

[0002] As a new type of material with antibacterial and bactericidal functions, antibacterial materials are used in people's daily lives. They can well establish a green barrier, improve the living environment, and reduce diseases. For example, disposable nonwoven fabrics for medical and sanitary products, disposable nonwoven fabrics for antifouling clothing, agricultural fabrics, furniture fabrics, linings for the shoe industry, bath balls / bath towels, artificial turf silk, carpets and other materials can be made into antibacterial products by adding one or more specific antibacterial agents during the production process.

[0003] The antibacterial agents currently used in the market are mainly inorganic antibacterial agents, which are generally carrier compounds such as zeolites, phosphates, soluble glass, hydroxyapatite, etc. that carry metal ions such as silver, copper, and zinc. The antibacterial components of metal ions have a sustained release effect due to their carrier mesopores or interlayer effects, showing excellent antibacterial and long-lasting properties. However, the above-mentioned loaded silver antibacterial agent has a large process control difficulty when added to polyolefin filamentary materials because its particle size is controlled at the micron level, generally 1-10μm, and it is difficult to control the process and wire drawing is difficult. In addition, the prepared antibacterial filamentary products are generally tested according to the antibacterial fiber product absorption method or the oscillation method. Because polyolefin filamentary products have poor water absorption, especially thicker filaments have worse water absorption, resulting in insufficient contact between the antibacterial components and the test strains, making it difficult to effectively exert the antibacterial effect of the material and its antibacterial rate difficult to meet the standard. Especially for disposable sanitary products, in actual use, the contact time period (generally required to be within 20 minutes) requires rapid antibacterial effect, while the conventional inorganic silver-loaded antibacterial components mentioned above need to be in contact for more than 4 hours to exert their antibacterial effect. In order to achieve the goal, researchers often achieve the goal by adding organic antibacterial agents with high bactericidal efficiency, but organic antibacterial agents such as quaternary ammonium salts, quaternary phosphonium salts, imidazoles, pyridines, and organic metals have the disadvantages of poor heat resistance, easy precipitation, low safety, etc., and are rarely used.

[0004] CN104553174A discloses a composite nonwoven material and a preparation method thereof. The composite nonwoven material of the invention comprises at least two layers of PP spunbond nonwoven material layers and a PA6 or PA66 electrostatically spun nanofiber material layer sandwiched between the two layers of PP spunbond nonwoven material layers. The surface of the composite nonwoven material is uniformly absorbed with ultraviolet absorbers and antibacterial agents; in the two layers of PP spunbond nonwoven material layers sandwiching the PA6 or PA66 electrostatically spun nanofiber material layer, at least one PP spunbond nonwoven material layer is coated with a nano titanium dioxide photocatalyst coating. The composite nonwoven material of the invention has high strength and low fiber fineness; it has high porosity, high specific surface area, good barrier and air permeability, anti-aging and antibacterial properties; compared with the nonwoven material of the blended spinning, there are no production and quality defects caused by uneven mixing or precipitation of additives; and the preparation method is simple, and general nonwoven material production equipment can be used. However, the durability, strength and softness of the antibacterial properties of the material need to be further improved. Summary of the invention

[0005] In view of the deficiencies of the prior art, the object of the present invention is to provide a photocatalyst nano antibacterial nonwoven material and a preparation method thereof. The prepared photocatalyst nano antibacterial nonwoven material has long-lasting and effective antibacterial performance, strength and softness.

[0006] One of the purposes of the present invention is to provide a photocatalyst nano antibacterial nonwoven material. To achieve this purpose, the present invention adopts the following technical solutions:

[0007] The photocatalyst nano antibacterial nonwoven material of the present invention comprises at least two layers of polypropylene antibacterial nanofiber nonwoven material layers, the surface of each layer of the polypropylene antibacterial nanofiber nonwoven material layer is coated with a nano photocatalyst composite coating, and a breathable layer is arranged between two adjacent layers of the polypropylene antibacterial nanofiber nonwoven material layers, and the breathable layer is provided with a plurality of micropores.

[0008] The photocatalyst nano antibacterial nonwoven material of the present invention has at least two layers of surfaces coated with nano photocatalyst composite coating polypropylene antibacterial nano fiber nonwoven material layers, so that the nonwoven material of the present invention has long-lasting and effective antibacterial performance. The air permeable layer provided with a plurality of micropores further increases the air permeability of the material and also makes the antibacterial property better. In addition, the photocatalyst nano antibacterial nonwoven material of the present invention has good strength and softness.

[0009] The micropores may be arranged randomly or in an array on the breathable layer.

[0010] The fiber fineness of the polypropylene antibacterial nanofiber nonwoven material layer is 1 to 3 deniers.

[0011] The thickness of the polypropylene antibacterial nanofiber nonwoven material layer is 0.4-0.5 mm, for example, the thickness of the polypropylene antibacterial nanofiber nonwoven material layer is 0.4 mm, 0.41 mm, 0.42 mm, 0.43 mm, 0.44 mm, 0.45 mm, 0.46 mm, 0.47 mm, 0.48 mm, 0.49 mm, or 0.5 mm.

[0012] The thickness of the nano-photocatalyst composite coating is 0.01-0.03 mm, for example, the thickness of the nano-photocatalyst composite coating is 0.01 mm, 0.015 mm, 0.02 mm, 0.025 mm, or 0.03 mm.

[0013] The thickness of the breathable layer is 0.4-0.5 mm, for example, the thickness of the breathable layer is 0.4 mm, 0.41 mm, 0.42 mm, 0.43 mm, 0.44 mm, 0.45 mm, 0.46 mm, 0.47 mm, 0.48 mm, 0.49 mm, or 0.5 mm.

[0014] The pore size of the micropore is 50-100 nm, for example, the pore size of the micropore is 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, or 100 nm.

[0015] The polypropylene antibacterial nanofiber nonwoven material layer comprises the following components by weight percentage:

[0016] The polypropylene resin is 90-95%, for example, the weight percentage of the polypropylene resin is 90%, 91%, 92%, 93%, 94%, 95%.

[0017] The masterbatch is 1-3%, for example, the weight percentage of the masterbatch is 1%, 1.5%, 2%, 2.5%, 3%.

[0018] The antibacterial masterbatch is 2-10%, for example, the weight percentage of the antibacterial masterbatch is 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.

[0019] By weight percentage, the antibacterial masterbatch is composed of 70-80% polypropylene resin, 5-15% nano zinc oxide, 1-10% guanidine polymer and 5-10% dispersant; for example, the weight percentage of polypropylene resin is 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, the weight percentage of nano zinc oxide is 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, the weight percentage of guanidine polymer is 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, and the weight percentage of dispersant is 5%, 6%, 7%, 8%, 9%, 10%.

[0020] Preferably, the guanidine polymer is polyhexamethyleneguanidine hydrochloride and / or polyhexamethylenebiguanide hydrochloride;

[0021] Preferably, the dispersant is fumed silica.

[0022] In terms of weight percentage, the nano-photocatalyst composite coating is composed of nano-titanium dioxide and nano-silver in a mass ratio of (1-3):1; for example, the mass ratio of nano-titanium dioxide and nano-silver is 1:1, 2:1, 3:1, etc. The usage ratio of the two can play a more efficient role within this range and have a better antibacterial effect.

[0023] Preferably, the particle size of the nano titanium dioxide is 5 to 50 nm, for example, the particle size of the nano titanium dioxide is 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, and 40 nm; the particle size of the nano silver is 10 to 100 nm, for example, the particle size of the nano silver is 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, and 100 nm.

[0024] The second object of the present invention is to provide a method for preparing a photocatalyst nano antibacterial nonwoven material, comprising the following steps:

[0025] 1) Preparing polypropylene antibacterial nanofiber nonwoven materials;

[0026] 2) coating the surface of the polypropylene antibacterial nanofiber nonwoven material obtained in step 1) with a nano-photocatalyst composite coating;

[0027] 3) A breathable layer with a plurality of micropores is arranged between at least two layers of the polypropylene antibacterial nanofiber nonwoven material coated with the nano photocatalyst composite coating in step 2), and the photocatalyst nano antibacterial nonwoven material is obtained by thermal bonding and composite.

[0028] Among them, the steps for preparing the polypropylene antibacterial nanofiber nonwoven material are as follows: polypropylene resin, masterbatch and antibacterial masterbatch are uniformly mixed according to the ratio, and process parameters such as upper roller temperature, lower roller temperature, rolling mill temperature, suction volume, and cold air start are adjusted. After heating, melting, plasticizing and mixing by a screw extruder, the mixture is accurately metered and transported to the die head by a metering pump. The melt is uniformly extruded through holes, and enters a stretcher after being cooled by cooling air. The filaments are sucked into the stretcher under the negative pressure of the stretcher, and a cloth surface is formed under the assistance of a suction fan. The cloth surface is pre-pressed by a sealing roller and then reinforced by thermal bonding treatment of a hot rolling mill.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] The preparation method of the photocatalyst nano antibacterial nonwoven material of the present invention is simple, and the prepared photocatalyst nano antibacterial nonwoven material has long-lasting and effective antibacterial performance, strength and softness, wherein the C4 dissolution antibacterial rate is greater than or equal to 95%, and the difference in the C5 non-dissolution antibacterial rate is greater than or equal to 25%; at 20g / cm 2 Taking the gram weight material as an example, the transverse tensile strength is greater than or equal to 27N, the longitudinal tensile strength is greater than or equal to 40N, and the softness is less than or equal to 35mN; the transverse and longitudinal elongation is greater than or equal to 92%, and the whiteness is greater than or equal to 92%. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 It is a schematic structural diagram of the photocatalyst nano antibacterial nonwoven material of the present invention;

[0032] Figure 2 for Figure 1 A schematic diagram of the structure of the breathable layer;

[0033] The reference numerals are as follows:

[0034] 1-polypropylene antibacterial nanofiber nonwoven material layer; 2-breathable layer; 3-nano-photocatalyst composite coating; 4-micropores. DETAILED DESCRIPTION

[0035] The following is combined with Figure 1-2 , and further illustrate the technical solution of the present invention through specific embodiments.

[0036] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0037] like Figure 1 , 2 As shown, the photocatalyst nano antibacterial nonwoven material of the present invention comprises at least two layers of polypropylene antibacterial nanofiber nonwoven material layers 1, the surface of each layer of the polypropylene antibacterial nanofiber nonwoven material layer 1 is coated with a nano photocatalyst composite coating 3, and a breathable layer 2 is arranged between two adjacent layers of the polypropylene antibacterial nanofiber nonwoven material layers 1, and the breathable layer is provided with a plurality of micropores 4.

[0038] Example 1

[0039] The photocatalyst nano antibacterial nonwoven material of this embodiment includes two layers of polypropylene antibacterial nanofiber nonwoven material layers, the surface of each layer of polypropylene antibacterial nanofiber nonwoven material layer is coated with a nano photocatalyst composite coating, and a breathable layer is arranged between two adjacent layers of polypropylene antibacterial nanofiber nonwoven material layers, and the breathable layer is provided with a plurality of micropores.

[0040] The fiber fineness of the polypropylene antibacterial nanofiber nonwoven material layer is 1 denier.

[0041] The thickness of each polypropylene antibacterial nanofiber nonwoven material layer is 0.47 mm, the thickness of the nano-photocatalyst composite coating is 0.02 mm, the thickness of the air-permeable layer is 0.42 mm, and the pore size of the micropores is 100 nm.

[0042] Wherein, the polypropylene antibacterial nanofiber nonwoven material layer comprises the following components by weight percentage:

[0043] Polypropylene resin 94%

[0044] Masterbatch 1%

[0045] Antibacterial masterbatch 5%.

[0046] Wherein, the antibacterial masterbatch is composed of 70% polypropylene resin, 10% nano zinc oxide, 10% guanidine polymer and 10% dispersant by weight, the guanidine polymer is polyhexamethylene biguanide hydrochloride, and the dispersant is fumed silica.

[0047] Wherein, in terms of weight percentage, the nano-photocatalyst composite coating is composed of nano-titanium dioxide and nano-silver in a mass ratio of 1:1; the particle size of the nano-titanium dioxide is 30 nm, and the particle size of the nano-silver is 20 nm.

[0048] The preparation method of the photocatalyst nano antibacterial nonwoven material of this embodiment comprises the following steps:

[0049] 1) Preparing polypropylene antibacterial nanofiber nonwoven materials;

[0050] 2) coating the surface of the polypropylene antibacterial nanofiber nonwoven material obtained in step 1) with a nano-photocatalyst composite coating;

[0051] 3) A breathable layer with a plurality of micropores is arranged between the two layers of the polypropylene antibacterial nanofiber nonwoven material coated with the nano photocatalyst composite coating in step 2), and the two layers are thermally bonded and composited to obtain the photocatalyst nano antibacterial nonwoven material.

[0052] Example 2

[0053] The photocatalyst nano antibacterial nonwoven material of this embodiment includes two layers of polypropylene antibacterial nanofiber nonwoven material layers, each layer of the polypropylene antibacterial nanofiber nonwoven material layer is coated with a nano photocatalyst composite coating, and a breathable layer is arranged between two adjacent layers of the polypropylene antibacterial nanofiber nonwoven material layer, and the breathable layer is provided with a plurality of micropores.

[0054] The fiber fineness of the polypropylene antibacterial nanofiber nonwoven material layer is 3 deniers.

[0055] The thickness of each polypropylene antibacterial nanofiber nonwoven material layer is 0.45 mm, the thickness of the nano-photocatalyst composite coating is 0.03 mm, the thickness of the air-permeable layer is 0.45 mm, and the pore size of the micropores is 80 nm.

[0056] Wherein, the polypropylene antibacterial nanofiber nonwoven material layer comprises the following components by weight percentage:

[0057] Polypropylene resin 95%

[0058] Masterbatch 2%

[0059] Antibacterial masterbatch 3%.

[0060] Among them, the antibacterial masterbatch is composed of 80% polypropylene resin, 10% nano zinc oxide, 5% guanidine polymer and 5% dispersant by weight, the guanidine polymer is a mixture of 2% polyhexamethyleneguanidine hydrochloride and 3% polyhexamethylenebiguanidine hydrochloride, and the dispersant is fumed silica.

[0061] Wherein, in terms of weight percentage, the nano-photocatalyst composite coating is composed of nano-titanium dioxide and nano-silver in a mass ratio of 2:1; the particle size of the nano-titanium dioxide is 40nm, and the particle size of the nano-silver is 50nm.

[0062] The preparation method of the photocatalyst nano antibacterial nonwoven material of this embodiment comprises the following steps:

[0063] 1) Preparing polypropylene antibacterial nanofiber nonwoven materials;

[0064] 2) coating the surface of the polypropylene antibacterial nanofiber nonwoven material obtained in step 1) with a nano-photocatalyst composite coating;

[0065] 3) A breathable layer with a plurality of micropores is arranged between the two layers of the polypropylene antibacterial nanofiber nonwoven material coated with the nano photocatalyst composite coating in step 2), and the two layers are thermally bonded and composited to obtain the photocatalyst nano antibacterial nonwoven material.

[0066] Example 3

[0067] The photocatalyst nano antibacterial nonwoven material of this embodiment includes three layers of polypropylene antibacterial nanofiber nonwoven material layers, each layer of the polypropylene antibacterial nanofiber nonwoven material layer is coated with a nano photocatalyst composite coating, and a breathable layer is arranged between two adjacent layers of the polypropylene antibacterial nanofiber nonwoven material layer, and the breathable layer is provided with a plurality of micropores.

[0068] The fiber fineness of the polypropylene antibacterial nanofiber nonwoven material layer is 3 deniers.

[0069] The thickness of each polypropylene antibacterial nanofiber nonwoven material layer is 0.5 mm, the thickness of the nano-photocatalyst composite coating is 0.01 mm, the thickness of the air-permeable layer is 0.48 mm, and the pore size of the micropores is 50 nm.

[0070] Wherein, the polypropylene antibacterial nanofiber nonwoven material layer comprises the following components by weight percentage:

[0071] Polypropylene resin 94%

[0072] Masterbatch 3%

[0073] Antibacterial masterbatch 3%.

[0074] Wherein, the antibacterial masterbatch is composed of 70% polypropylene resin, 15% nano zinc oxide, 8% guanidine polymer and 7% dispersant by weight, the guanidine polymer is polyhexamethyleneguanidine hydrochloride, and the dispersant is fumed silica.

[0075] Wherein, in terms of weight percentage, the nano-photocatalyst composite coating is composed of nano-titanium dioxide and nano-silver in a mass ratio of 2:1; the particle size of the nano-titanium dioxide is 50nm, and the particle size of the nano-silver is 70nm.

[0076] The preparation method of the photocatalyst nano antibacterial nonwoven material of this embodiment comprises the following steps:

[0077] 1) Preparing polypropylene antibacterial nanofiber nonwoven materials;

[0078] 2) coating the surface of the polypropylene antibacterial nanofiber nonwoven material obtained in step 1) with a nano-photocatalyst composite coating;

[0079] 3) A breathable layer with a plurality of micropores is arranged between the three layers of the polypropylene antibacterial nanofiber nonwoven material coated with the nano-photocatalyst composite coating in step 2), and the photocatalyst nano-antibacterial nonwoven material is obtained by thermal bonding and composite.

[0080] Example 4

[0081] The photocatalyst nano antibacterial nonwoven material of this embodiment includes two layers of polypropylene antibacterial nanofiber nonwoven material layers, each layer of the polypropylene antibacterial nanofiber nonwoven material layer is coated with a nano photocatalyst composite coating, and a breathable layer is arranged between two adjacent layers of the polypropylene antibacterial nanofiber nonwoven material layer, and the breathable layer is provided with a plurality of micropores.

[0082] Wherein, the fiber fineness of the polypropylene antibacterial nanofiber nonwoven material layer is 2 denier.

[0083] The thickness of each polypropylene antibacterial nanofiber nonwoven material layer is 0.5 mm, the thickness of the nano-photocatalyst composite coating is 0.01 mm, the thickness of the air-permeable layer is 0.48 mm, and the pore size of the micropores is 50 nm.

[0084] Wherein, the polypropylene antibacterial nanofiber nonwoven material layer comprises the following components by weight percentage:

[0085] Polypropylene resin 92%

[0086] Masterbatch 1%

[0087] Antibacterial masterbatch 7%.

[0088] Wherein, by weight percentage, the antibacterial masterbatch is composed of 78% polypropylene resin, 12% nano zinc oxide, 2% guanidine polymer and 8% dispersant, the guanidine polymer is 1% polyhexamethylene guanidine hydrochloride and 1% polyhexamethylene biguanide hydrochloride, and the dispersant is fumed silica.

[0089] Wherein, in terms of weight percentage, the nano-photocatalyst composite coating is composed of nano-titanium dioxide and nano-silver in a mass ratio of 3:1; the particle size of the nano-titanium dioxide is 40nm, and the particle size of the nano-silver is 70nm.

[0090] The preparation method of the photocatalyst nano antibacterial nonwoven material of this embodiment comprises the following steps:

[0091] 1) Preparing polypropylene antibacterial nanofiber nonwoven materials;

[0092] 2) coating the surface of the polypropylene antibacterial nanofiber nonwoven material obtained in step 1) with a nano-photocatalyst composite coating;

[0093] 3) A breathable layer with a plurality of micropores is arranged between the two layers of the polypropylene antibacterial nanofiber nonwoven material coated with the nano photocatalyst composite coating in step 2), and the two layers are thermally bonded and composited to obtain the photocatalyst nano antibacterial nonwoven material.

[0094] Example 5

[0095] The photocatalyst nano antibacterial nonwoven material of this embodiment includes two layers of polypropylene antibacterial nanofiber nonwoven material layers, each layer of the polypropylene antibacterial nanofiber nonwoven material layer is coated with a nano photocatalyst composite coating, and a breathable layer is arranged between two adjacent layers of the polypropylene antibacterial nanofiber nonwoven material layer, and the breathable layer is provided with a plurality of micropores.

[0096] The fiber fineness of the polypropylene antibacterial nanofiber nonwoven material layer is 3 deniers.

[0097] The thickness of each polypropylene antibacterial nanofiber nonwoven material layer is 0.47 mm, the thickness of the nano-photocatalyst composite coating is 0.02 mm, the thickness of the air-permeable layer is 0.45 mm, and the pore size of the micropores is 100 nm.

[0098] Wherein, the polypropylene antibacterial nanofiber nonwoven material layer comprises the following components by weight percentage:

[0099] Polypropylene resin 94%

[0100] Masterbatch 3%

[0101] Antibacterial masterbatch 3%.

[0102] Wherein, by weight percentage, the antibacterial masterbatch is composed of 80% polypropylene resin, 10% nano zinc oxide, 5% guanidine polymer and 5% dispersant, the guanidine polymer is polyhexamethyleneguanidine hydrochloride and / or polyhexamethylenebiguanidine hydrochloride, and the dispersant is fumed silica.

[0103] Wherein, in terms of weight percentage, the nano-photocatalyst composite coating is composed of nano-titanium dioxide and nano-silver in a mass ratio of 2:1; the particle size of the nano-titanium dioxide is 20 nm, and the particle size of the nano-silver is 30 nm.

[0104] The preparation method of the photocatalyst nano antibacterial nonwoven material of this embodiment comprises the following steps:

[0105] 1) Preparing polypropylene antibacterial nanofiber nonwoven materials;

[0106] 2) coating the surface of the polypropylene antibacterial nanofiber nonwoven material obtained in step 1) with a nano-photocatalyst composite coating;

[0107] 3) A breathable layer with a plurality of micropores is arranged between at least two layers of the polypropylene antibacterial nanofiber nonwoven material coated with the nano photocatalyst composite coating in step 2), and the photocatalyst nano antibacterial nonwoven material is obtained by thermal bonding and composite.

[0108] Example 6

[0109] The difference between this embodiment and embodiment 1 is that the fiber fineness of the polypropylene antibacterial nanofiber nonwoven material layer is 5 deniers, and the rest is the same as embodiment 1.

[0110] Example 7

[0111] The difference between this embodiment and embodiment 1 is that, by weight percentage, the polypropylene antibacterial nanofiber nonwoven material layer comprises the following components:

[0112] Polypropylene resin 94%

[0113] Masterbatch 5%

[0114] Antibacterial masterbatch 1%.

[0115] Example 8

[0116] The difference between this embodiment and embodiment 1 is that, by weight percentage, the antibacterial masterbatch does not contain guanidine polymer, the reduced weight percentage of guanidine polymer is added to the nano zinc oxide, and the rest is the same as embodiment 1.

[0117] Example 9

[0118] The difference between this embodiment and embodiment 1 is that, by weight percentage, the antibacterial masterbatch does not contain nano zinc oxide, the weight percentage of the reduced nano zinc oxide is increased to the mesoguanidine polymer, and the rest is the same as embodiment 1.

[0119] Example 10

[0120] The difference between this embodiment and embodiment 1 is that the guanidine-based polymer is polyhexamethyleneguanidine hydrochloride, and the other aspects are the same as those of embodiment 1.

[0121] Embodiment 11

[0122] The difference between this embodiment and embodiment 1 is that the nano-photocatalyst composite coating is a nano-titanium dioxide layer, and the rest is the same as embodiment 1.

[0123] Example 12

[0124] The difference between this embodiment and the first embodiment is that the nano-photocatalyst composite coating is a nano-silver layer, and the rest is the same as the first embodiment.

[0125] Example 13

[0126] The difference between this embodiment and embodiment 1 is that the mass ratio of nano-titanium dioxide to nano-silver is 5:1, and the other aspects are the same as those of embodiment 1.

[0127] Comparative Example 1

[0128] The difference between this comparative example and Example 1 is that the surface of the polypropylene antibacterial nanofiber nonwoven material layer is not coated with the nano-photocatalyst composite coating, and the rest is the same as Example 1.

[0129] Comparative Example 2

[0130] The difference between this comparative example and Example 1 is that no air permeable layer is provided between two adjacent layers of the polypropylene antibacterial nanofiber nonwoven material.

[0131] The photocatalyst nano antibacterial nonwoven materials prepared in Examples 1-13 and the antibacterial nonwoven materials prepared in Comparative Examples 1-2 were subjected to performance tests. The test results are shown in Table 1.

[0132] Among them, the test standards for C4 dissolution antibacterial performance and C5 non-dissolution antibacterial performance are carried out in accordance with GB15979-2002, "inhibition rate" refers to the inhibition rate of the test sample and the control sample (%), and "inhibition rate difference" refers to the difference in inhibition rate between the test sample and the control sample (%). The test standard for tensile strength is carried out in accordance with GB / T 24218.3-2010, the test standard for softness is carried out in accordance with GB / T8942-2002, the test standard for uniformity is carried out in accordance with GB / T 24218.2-2009, the test standard for elongation is carried out in accordance with GB / T24218.3-2010, and the test standard for whiteness is carried out in accordance with GB / T 8424.2-2001.

[0133] Table 1

[0134]

[0135]

[0136] The preparation method of the photocatalyst nano antibacterial nonwoven material of the present invention is simple, and the prepared photocatalyst nano antibacterial nonwoven material has long-lasting and effective antibacterial performance, strength and softness, wherein the C4 dissolution antibacterial rate is greater than or equal to 95%, and the difference in the C5 non-dissolution antibacterial rate is greater than or equal to 25%; at 20g / cm 2 Taking the gram weight material as an example, the transverse tensile strength is greater than or equal to 27N, the longitudinal tensile strength is greater than or equal to 40N, and the softness is less than or equal to 35mN; the transverse and longitudinal elongation is greater than or equal to 92%, and the whiteness is greater than or equal to 92%.

[0137] The fiber fineness of the polypropylene antibacterial nanofiber nonwoven material layer in Example 6 is too large, which will reduce the strength of the material; the amount of antibacterial masterbatch used in Example 7 is reduced, the antibacterial masterbatch in Example 8 does not contain guanidine polymer, and the antibacterial masterbatch in Example 9 does not contain nano zinc oxide, all of which will deteriorate the antibacterial performance of the material; the guanidine polymer in Example 10 is replaced by polyhexamethylene guanidine hydrochloride, which will also deteriorate the antibacterial performance of the material; the nano-photocatalyst composite coating in Example 11 is only a nano-titanium dioxide layer, the nano-photocatalyst composite coating in Example 12 is only a nano-silver layer, and the mass ratio of nano-titanium dioxide and nano-silver in Example 13 is not within the specified range of the present application, all of which will have an adverse effect on the antibacterial performance of the material.

[0138] In Comparative Example 1, the surface of the polypropylene antibacterial nanofiber nonwoven material layer is not coated with a nano-photocatalyst composite coating, which greatly reduces the antibacterial performance of the material; in Comparative Example 2, no breathable layer is provided, which also reduces the antibacterial performance of the material.

[0139] The present invention illustrates the detailed process equipment and process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process equipment and process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A photocatalyst antibacterial nano nonwoven material, characterized in that: The invention comprises at least two layers of polypropylene antibacterial nanofiber nonwoven material, the surface of each layer of the polypropylene antibacterial nanofiber nonwoven material is coated with a nano-photocatalyst composite coating, and a breathable layer is arranged between two adjacent layers of the polypropylene antibacterial nanofiber nonwoven material, and the breathable layer is provided with a plurality of micropores; In terms of weight percentage, the nano-photocatalyst composite coating is composed of nano-titanium dioxide and nano-silver in a mass ratio of (1-3):1; The polypropylene antibacterial nanofiber nonwoven material layer comprises the following components by weight percentage: Polypropylene resin 90~95% Masterbatch 1~3% Antibacterial masterbatch 2-10%; In terms of weight percentage, the antibacterial masterbatch is composed of 70-80% polypropylene resin, 5-15% nano zinc oxide, 1-10% guanidine polymer and 5-10% dispersant; the guanidine polymer is polyhexamethyleneguanidine hydrochloride and / or polyhexamethylenebiguanidine hydrochloride; The fiber fineness of the polypropylene antibacterial nanofiber nonwoven material layer is 1 to 3 deniers.

2. The photocatalyst antibacterial nano nonwoven material according to claim 1, characterized in that: The thickness of the polypropylene antibacterial nanofiber nonwoven material layer is 0.4-0.5 mm.

3. The photocatalyst antibacterial nano nonwoven material according to claim 1, characterized in that: The thickness of the nano-photocatalyst composite coating is 0.01-0.03 mm.

4. The photocatalyst antibacterial nano nonwoven material according to claim 1, characterized in that: The thickness of the air permeable layer is 0.4-0.5 mm.

5. The photocatalyst antibacterial nano nonwoven material according to claim 1, characterized in that: The pore diameter of the micropores is 50-100 nm.

6. The photocatalyst antibacterial nano nonwoven material according to claim 1, characterized in that: The dispersant is fumed silica.

7. The photocatalyst antibacterial nano nonwoven material according to claim 1, characterized in that: The particle size of the nano titanium dioxide is 5 to 50 nm, and the particle size of the nano silver is 10 to 100 nm.

8. A method for preparing the photocatalyst nano antibacterial nonwoven material according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: 1) Preparing polypropylene antibacterial nanofiber nonwoven materials; 2) coating the surface of the polypropylene antibacterial nanofiber nonwoven material obtained in step 1) with a nano-photocatalyst composite coating; 3) A breathable layer with a plurality of micropores is arranged between at least two layers of the polypropylene antibacterial nanofiber nonwoven material coated with the nano photocatalyst composite coating in step 2), and the photocatalyst nano antibacterial nonwoven material is obtained by thermal bonding and composite.

Citation Information

Patent Citations

  • Antibacterial polypropylene plastic and preparation method thereof

    CN102838809A

  • Composite nonwoven material and preparation method thereof

    CN104553174A

  • Antibacterial fabric

    CN202786881U

  • Photocatalyst nano antibacterial non-woven material

    CN210362822U